Dynamics and control of cavitation during high-intensity focused ultrasound application - Thomas, C; Farny, C; Coussios, C; Roy, R; Holt, R (Acoustical Society of America, 2005)
In this paper the results of two studies related to high-intensity focused ultrasound (HIFU) and cavitation are reported. The first study described used polyacrylamide phantoms to gain insight into the behavior of cavitation activity in the focal region of the HIFU transducer. Results indicate that cavitation is the source of a previously observed enhanced heating effect in HIFU. The second study discussed used agar-graphite phantoms to see if changing the duty cycle of the driving could effect some measure of control over the cavitation activity; the results indicate that it can.